A comparative study of issues and problems of young interfaith married couples and old interfaith married couples - Muñoz, Beteena Rae M.; Reyes, Clarissa F.; Naraval, Elizandra Philippa E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT This study is a qualitative research that aimed to determine the issues and problems, as well as a comparison on how these were resolved by Young Interfaith Married Couples (YIMC)and Old Interfaith Married Couples (OIMC). Data was gathered using a semi-structured interview given to 16 couples, eight YIMC and eight OIMC respectively. Results showed that both YIMC and OIMC have issues and problems when it comes to married life based on these aspects: Religious Commitment (RC), Relationship with Family, Friends and Community (RFFC), Decision Making (DC) and Religious Identification of the Child (RIC). Based from the data, it consistently showed that the wives from both groups gave more issues and problems as compared to the husbands, which means they were more open to sharing their experiences. The comparison of the YIMC and OIMC exhibited that the presence of issues and problems was most prevalent in the aspect of Religious Commitment specifically Church Attendance, Religious Beliefs and Religious Practices. However, the YIMC had encountered these issues more often than the OIMC. This may be related to the period of adjustment that newly married couples experience. Likewise, there were also similarities in the way they cope with their issues and problems despite the variety of responses they shared. Overall, in both groups, there were still more respondents who did not mention any issue and problem, thus they are able to live normal lives just like any married couple despite having different religions.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Interfaith marriage -- Philippines